In the Classzoom: On the Spatiality of Online Teaching - Leone, Massimo (E|C, 2021)
The paper consists in an in-depth semiotic analysis of the spatiality of present-day online teaching as compared with that of the traditional classroom. Its spatiality, the paper contends, cannot be properly digitalized, because it is strictly dependent on embodiment. The embodied spatiality of a classroom, it is argued, is nevertheless fundamental to bring about the ritual transfiguration that underpins the didactic experience and its socio-cultural functions. Hence, the urgent need to rethink digital teaching environments in relation to these crucial lacks, which only semiotics, with its specific attention to nonverbal elements of communication — including spatiality — is fully equipped to detect.